Suitability of Different Titanium Dioxide Nanotube Morphologies for Photocatalytic Water Treatment - Clayton Farrugia; Alessandro Di Mauro; Frederick Lia; Edwin Zammit; Alex Rizzo; Vittorio Privitera; Giuliana Impellizzeri; Maria Antonietta Buccheri; Giancarlo Rappazzo; Maurice Grech; Paul Refalo; Stephen Abela (Nanomaterials, 2021)
Photocatalysis has long been touted as one of the most promising technologies for environmental remediation. The ability of photocatalysts to degrade a host of different pollutants, especially recalcitrant molecules, is certainly appealing. Titanium dioxide (TiO2) has been used extensively for this purpose. Anodic oxidation allows for the synthesis of a highly ordered nanotubular structure with a high degree of tunability. In this study, a series of TiO2 arrays were synthesised using different electrolytes and different potentials. Mixed anatase-rutile photocatalysts with excellent wettability were achieved with all the experimental iterations. Under UVA light, all the materials showed significant photoactivity towards different organic pollutants. The nanotubes synthesised in the ethylene glycol-based electrolyte exhibited the best performance, with near complete degradation of all the pollutants. The antibacterial activity of this same material was similarly high, with extremely low bacterial survival rates. Increasing the voltage resulted in wider and longer nanotubes, characteristics which increase the level of photocatalytic activity. The ease of synthesis coupled with the excellent activity makes this a viable material that can be used in flat-plate reactors and that is suitable for photocatalytic water treatment.